Simple spectrophotometric determination of monopersulfate - Wacławek, S; Grübel, K; Černík, M (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2015)
A simple, sensitive and accurate spectrophotometric method has been developed and validated for the determination of monopersulfate (MPS) which is an active part of potassium monopersulfate triple salt that has the commercial name - Oxone. This work proposes a spectrophotometric determination of monopersulfate based on modification of the iodometric titration method. The analysis of absorption spectra was made for the concentration range from 1.35 to 13.01 ppm of MPS (with a detection and quantification limit of 0.41 and 1.35 ppm, respectively) and different pH values. The influence of several anions on the measurement was also investigated. Furthermore, the absorbance of iron and cobalt (often used as free radical initiators) proved to have no effect on the measurement of MPS concentrations. On the basis of the conducted studies, we propose 395 nm as an optimal wavelength for the determination of MPS concentrations.
Keywords: Potassium peroxymonosulfate; Monopersulfate (MPS); Iodometric titration; Spectrophotometry; Oxone; Remediation